Determinants of frontline employee service innovative behavior: The moderating role of co-worker socializing and service climate. Issue 9 (16th September 2019) - Al-Hawari, Mohd A.; Bani-Melhem, Shaker; Shamsudin, Faridahwati Mohd
Abstract : Purpose: The purpose of this study is to examine the influence of workplace happiness and work engagement on employee service innovative behavior from the perspective of positive psychology. The study also examines if work engagement mediates the relationship between workplace happiness and employee service innovative behavior. Finally, it investigates how co-worker socializing and the service climate of the organization moderate the relationship between work engagement and employee service innovative behavior. Design/methodology/approach: The study used survey data from 321 frontline employees working in the service sector in the United Arab Emirates (UAE). Six major hypotheses were established and examined using the SPSS Statistics V22.0 Process. The measurement model was analyzed using Amos 22. Findings: Workplace happiness and work engagement are found to be important factors affecting employee service innovative behavior. Workplace happiness influences employee service innovative behavior directly and indirectly through work engagement. Both service climate and co-worker socializing play a significant moderating role in the relationship between work engagement and employee service innovative behavior among frontline employees. Interestingly, service climate erodes this relationship while co-worker socializing enhances it. Practical implications: This study provides guidelines for managers and practitioners in the service industry to promote frontline employee service innovative behavior. Specifically, the findings provide guidance for decision-makers on how to use workplace happiness to trigger the innovative service behaviors of frontline employees, taking into consideration the conditional role of service climate and co-worker socializing. Originality/value: The literature on factors affecting the service innovative behavior of frontline employees in the service sector from the perspective of positive psychology is limited, especially in the context of the UAE. The data, framework and outcomes of this research address this gap and contribute to the current body of knowledge. Specifically, the study contributes to the broaden-and-build theory of positive emotions in the field of positive psychology by validating the applicability of the theory in a wider organizational context.